Neuromuscular electrical stimulation is ineffective for treating quadriceps muscle wasting with ruptured aneurysm: A case report. (November 2018) - Nozoe, Masafumi; Kamo, Arisa; Shimada, Shinichi; Mase, Kyoshi
Abstract: Introduction: Neuromuscular electrical stimulation (NMES) is a preventive intervention for muscle wasting in patients with aneurysms during the acute phase; however, its efficacy still remains unclear. In this case study, we report the effects of NMES on quadriceps muscle wasting for a patient with ruptured middle cerebral artery aneurysms during the acute phase. Presentation of case: A 66-year-old woman was admitted because of a ruptured middle cerebral artery aneurysm resulting from intracerebral hematoma with subarachnoid hemorrhage. The following day, the patient started undergoing 60–120-min NMES treatment for both her quadriceps muscles, which was continued for 10 days in 2 weeks. Quadriceps muscle thickness as measured by ultrasonography was decreased in both sides (26% and 35% for the right and left sides, respectively). The compound muscle action potential (CMAP) amplitude in the peroneal nerve was also decreased in both sides (73% vs 76%). Discussion: The lack of efficacy of NMES in preventing muscle wasting is the decreased CMAP amplitude in this patient, which showed the possibility of existence of critical illness polyneuropathy. Conclusion: NMES had no effect on quadriceps muscle wasting in a patient with ruptured middle cerebral artery aneurysms who had decreased CMAP amplitude in the peroneal nerve during the acute phase. NMES is not effective for patients with peripheral nerve conduction abnormalities. Highlights: NMES is not effective for preventing muscle wasting and disability. NMES is not effective for patients with peripheral nerve conduction abnormalities. The efficacy of NMES is dependent on whether conduction abnormalities exist.